Adapting Esu Reportage Tactics in some Terrorism Media Reports in Nigeria - Oriola, Titilope Oluwaseun (NIU Journal of Humanities; Vol 5 No 2 (2020): KIU Journal of Humanities, Vol. 5 No. 2, June 2020, 2020)
The activity of the media reporter in Nigeria is synonymous to the African traditional Esu , versatile, clever and witty. Previous studies on Media Terrorism Discourse have focused more on the bias and ideology of the media in such fields as linguistics, stylistics, critical discourse analysis and sociology but have largely neglected the socio-religious component of the media reportage on terrorism which would have facilitated useful cues in understanding and tackling the malaise of terrorism in Nigeria especially. This paper is therefore designed to investigate socio-religious strategies, ideologies and context in terrorism media reports with a view to establishing a connection between modern media terrorism reportage and African traditional belief of reportage. Odebunmiâ€™s Pragmatic Strategies together with Odu Irete-Egutan comprising socio-religious strategies such as false attraction, sympathy through fraudulent means, false impression of innocence and harmlessness was adopted as a theoretical framework for the study. Fifty recent Boko Haram terrorism texts in Nigerian Guardian Newspaper were selected and examined purposively. The analysis showed that three strategies utilized by Esu in the Ifa corpus of Irete-Egutan are evident in the modern media reportage. The work therefore concluded that the knowledge of traditional reportage would facilitate a better understanding of modern terrorism study. Keywords: Irete-Egutan, pragmatic strategies,  Ifa chronicles/corpus, terrorism media reportage, Boko Haram